2014
DOI: 10.1161/strokeaha.114.007362
|View full text |Cite|
|
Sign up to set email alerts
|

Pathogenic Ischemic Stroke Phenotypes in the NINDS-Stroke Genetics Network

Abstract: Background and Purpose NINDS Stroke Genetics Network (SiGN) is an international consortium of ischemic stroke studies that aims to generate high quality phenotype data to identify the genetic basis of etiologic stroke subtypes. This analysis characterizes the etiopathogenetic basis of ischemic stroke and reliability of stroke classification in the consortium. Methods Fifty-two trained and certified adjudicators determined both phenotypic (abnormal test findings categorized in major etiologic groups without w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 18 publications
(27 reference statements)
0
30
0
1
Order By: Relevance
“…SiGN participants have been described elsewhere 21, 24 . Briefly, their mean age was 67 years, half (49%) were women, and White participants comprised 79%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SiGN participants have been described elsewhere 21, 24 . Briefly, their mean age was 67 years, half (49%) were women, and White participants comprised 79%.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, their mean age was 67 years, half (49%) were women, and White participants comprised 79%. Twenty-five percent had diabetes, 68% had hypertension, and 23% had coronary artery disease 24 .…”
Section: Resultsmentioning
confidence: 99%
“…) or interfere with the vascular risk factors. But apart from the above mentioned monogenic disorders, the current genomic technology is unlikely to improve assessment of stroke risk profile (7).…”
Section: Risk Factorsmentioning
confidence: 99%
“…The use of subtype classifi cation system helps to understand the differences in frequency of various stroke risk factors, incidence, strokeprognosis, chancesof recurrence, and long-termsurvival among different is chemic stroke subtypes. 2 The TOAS Tinvestigatorsdevised aseries of defi nitions to classify patients with is chemic stroke into 5 coreetiologic groupings:(1) Largeartery atherosclerosis, (2) Small artery occlusion(lacune), (3) Cardioembolism, (4) Stroke of other determined etiology, (5) Stroke of undetermined etiology, based on clinical impression and diagnostic fi ndings. 1 Studies of survival and recurrence after stroke have been reported throughout the world, 4,5,11,15,16 but there is limited data from Nepal on outcomes for individual subtypes of ischemic stroke.…”
mentioning
confidence: 99%